2011
DOI: 10.4236/ampc.2011.12004
|View full text |Cite
|
Sign up to set email alerts
|

Random Laser of R6G Dye and TiO<sub>2</sub> Nanoparticals Doped in PMMA Polymer

Abstract: The random laser (RL) based on organic Rhodamine 6G (R6G) laser-dye and Titanium dioxide (TiO2) suspended nanoparticles have been prepared with polymethylmethacrylate (PMMA) as a host. Both liquid and spray-coated homogeneous film samples of 22.4 µm-30.1 µm thickness range were use. Optimum concentrations have been determined depending on the normal fluorescence spectra which give evidence that the laser dye provides amplification and TiO 2 nanoparticles as scatter center. At the optimum concentrations, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Increasing the NP concentration causes the FWHM to collapse to its lasing value at a much faster rate and, once lasing, the FWHM is smaller for higher NP concentrations. These effects are consistent with previous measurements of other Rh6G NP/host combinations [26][27][28].…”
Section: A Linewidth Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…Increasing the NP concentration causes the FWHM to collapse to its lasing value at a much faster rate and, once lasing, the FWHM is smaller for higher NP concentrations. These effects are consistent with previous measurements of other Rh6G NP/host combinations [26][27][28].…”
Section: A Linewidth Measurementssupporting
confidence: 93%
“…From Tables I and II we see that the lasing threshold decreases as either the dye and/or particle concentration increases. These results are consistent with our FWHM measurements and previous measurements of RL in different Rh6G dye-doped NP/host combinations [27,28]. Plotting the threshold values from Table I NP concentration (see Figure 7) we find that the threshold depends on the particle concentration via a power function of the form…”
Section: B Lasing Thresholdsupporting
confidence: 92%
“…The results of random laser measurements show that the minimum band width at FWHM was 11 nm at 25 mJ and laser threshold at 3 mJ for a homogeneous silica xerogel sample doped with 10 −4 mol/l of R610 dye and 4.5 × 10 13 cm −3 of TiO 2 . This threshold was considered to be lower than that of organic hosts such as polymers [25]. It was also found that titanium particles contribute for small photodegradation of the dye molecules.…”
Section: Resultsmentioning
confidence: 99%
“…As of late, different interchanges, natural, biomedical, and space applications have been created by using irregular addition media as laser sources known as "random lasers" [1]. Additionally, the continuous and extraordinary improvements in nanotechnology have prompted uncommon advancements in the plan and manufacture of irregular increase media [2][3]. 8-Hydroxyquinoline zinc has many advantages, such as simple synthesis conditions [4].…”
Section: ■ Introductionmentioning
confidence: 99%